Identifikasi Kadar Pengawet Natrium Benzoate pada Saus Tomat yang Beredar di Wilayah Kabupaten Dompu - Nurislamiah, Nurislamiah; Martuti, Sri; Nailufar, Yuyun (Pusat Riset dan Inovasi Nasional, 2026)
Tomato sauce is a popular processed food product often added with preservatives to extend shelf life. Sodium benzoate is one of the most commonly used preservatives; however, its use must comply with the maximum limit set by BPOM, which is 1000 mg/kg. Excessive intake may cause health problems such as carcinogenic benzene formation and nervous system disorders. This study aimed to identify the sodium benzoate content in tomato sauces sold in Dompu Regency and evaluate their compliance with food safety standards. A descriptive quantitative method with a cross-sectional approach was applied. Five brands of tomato sauce were randomly selected from markets and minimarkets, then analyzed at the Toxicology Laboratory of Universitas ‘Aisyiyah Yogyakarta using UV-Vis spectrophotometry. The results showed sodium benzoate levels of 69.25 mg/kg in sample A, 1,653 mg/kg in DB, 263.7 mg/kg in DM, 166.5 mg/kg in JT, and 1,028 mg/kg in ML. Two of the five samples (DB and ML) exceeded the maximum permissible limit. These findings indicate that some tomato sauce products in Dompu Regency do not meet food safety standards, highlighting the need for stricter supervision to protect consumers.